Lean Manufacturing Implementation to Reduce Waste in Small-Scale Manufacturing Enterprises - Pratama, Ahmad Rizky; Dahab, Amr; Caldera, Savindi (RESWARA: Jurnal Riset Ilmu Teknik, 2024)
Small-scale manufacturing enterprises (SMEs) face persistent challenges related to inefficiency, high operational costs, and excessive waste generation, which threaten their competitiveness and long-term sustainability. Lean manufacturing has been widely recognized as an effective managerial and operational approach to reduce waste and enhance productivity; however, its implementation in small-scale manufacturing environments remains uneven and context-dependent. This study aims to analyze the implementation of lean manufacturing practices in small-scale manufacturing enterprises and evaluate their effectiveness in reducing operational waste. Using a qualitative case study approach supported by descriptive quantitative indicators, this research synthesizes empirical evidence from multiple manufacturing SMEs. Data were collected through direct observation, semi-structured interviews, document analysis, and performance measurement tools such as Overall Equipment Effectiveness (OEE) and Value Stream Mapping (VSM). The results demonstrate that the systematic application of lean tools—particularly 5S, VSM, Kaizen, and standardized work—significantly reduced non-value-added activities, shortened lead time, and improved equipment efficiency. Comparative analysis with previous studies confirms that lean implementation in SMEs contributes to measurable waste reduction and operational performance improvement, despite constraints related to resources and organizational culture. The study concludes that lean manufacturing is a viable and scalable strategy for small-scale manufacturing enterprises, provided that managerial commitment and continuous improvement culture are effectively cultivated.